The Effect Of Bkn E-Kinerja And Competence On Civil Servant Performance From The Perspective Of Information Technology In Human Resource Management (IT IN HRM) At Balai Monitor Spektrum Frekuensi Radio Kelas Ii Banjarmasin - Ramadhika Trisnasari; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The digital transformation of human resource management in the public sector has become a strategic instrument in improving organizational effectiveness, efficiency, transparency, and accountability. In Indonesia, one of the major digital innovations in public human resource management is the implementation of the E-kinerja system developed by the National Civil Service Agency (BKN). This system is designed to digitalize performance planning, reporting, and evaluation of civil servants. This study aims to examine the effect of BKN E-kinerja and employee competence on civil servant performance at Balai Monitor Spektrum Frekuensi Radio Kelas II Banjarmasin using the Information Technology in Human Resource Management (IT in HRM) framework. This study employed a quantitative approach with an explanatory research design. The population consisted of 31 civil servants, and saturated sampling was applied. Data were collected through questionnaires, interviews, and documentation, and analyzed using multiple linear regression. The results indicate that BKN E-kinerja has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance, and both variables simultaneously have a significant effect on employee performance. This study contributes theoretically to the development of IT in HRM in the public sector and provides practical implications for improving digital-based performance management systems. Keywords: E-Performance, Competence, Employee Performance, IT in HRM, Digital Human Resource Management